2005
DOI: 10.1007/s00415-005-0023-9
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic discrimination of dementia with Lewy bodies and Parkinson's disease with dementia

Abstract: SN hyperechogenicity is typical for PDD and DLB. However, size, asymmetry and relation of SN hyperechogenicity to age at disease onset discriminate PDD from DLB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 41 publications
7
47
2
1
Order By: Relevance
“…In patients with DLBD and PDD the width of the third ventricle and frontal horn was signifi cantly larger than for PD patients without dementia. This enlargement correlated with UPDRS scale in PDD 47 .…”
Section: Dementia With Lewy Bodiessupporting
confidence: 57%
“…In patients with DLBD and PDD the width of the third ventricle and frontal horn was signifi cantly larger than for PD patients without dementia. This enlargement correlated with UPDRS scale in PDD 47 .…”
Section: Dementia With Lewy Bodiessupporting
confidence: 57%
“…Patients with LBD [60] and CBD [26] have been reported to share the same echo feature with IPD patients. However, the hyperechogenicity of the LN is commonly seen in patients with CBD whereas patients with IPD only rarely have this feature.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, their sensitivity and specificity are not sufficiently high [8,24]. Moreover, neuroimaging methods, such as CT, MRI and PET, do not discriminate between IPD and DLB [60].…”
Section: Tcs In Apsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to PD, corticobasal ganglionic degeneration (CBD), DLB and many other neurodegenerative diseases also have SN+. Walter et al [19] believed that the features of SN+ of DLB are the areas of SN+ ≥ 0.25cm 2 , and the bilateral asymmetry index <1.15. It is suggested that the SN+ is related to iron metabolism rather than Lewy body accumulation.…”
Section: Discussionmentioning
confidence: 99%